Habitat Preferences of the Chinese Pangolin (Manis pentadactyla) in Southern Sankhuwasabha, Nepal - Dahal, Kishor (Academic Journal of Sukuna, 2025)
A field survey was conducted in September - October 2023 to assess the habitat preferences of pangolins in Madi Municipality, Sankhuwasabha. Using six (500 m ´ 500 m) transect strips across forest and cropland habitats, 20 pangolin burrows were recorded, 16 in forests (bamboo, Nepalese alder, grassland) and 4 in croplands (millet, paddy, tea).  Most burrows were found in grey soils and near water sources, indicating specific habitat preferences. These findings suggest that conservation efforts should prioritize forest habitats and areas near water sources to ensure the protection of pangolin populations.